Ectopic Expression of the Allium cepa 1-SST Gene in Cotton Improves Drought Tolerance and Yield Under Drought Stress in the Field - Liu, RuiNa; Jiao, TianQi; Zhang, ZeXing; Yao, Zhang; Li, ZhongQing; Wang, Saisai; Xin, Hongliang; Li, YuXia; Wang, AiYing; Zhu, JianBo (Frontiers in Plant Science, 2022)
In some plants, sucrose: sucrose 1-fructosyltransferase (1-SST) is the first irreversible key enzyme in fructan biosynthesis. Studies have shown that fructan accumulation enhances abiotic stress tolerance of plants. To investigate the role of 1-SST in drought stress responses, a total of 37 cotton plants expressing a 1-SST gene from Allium cepa were developed by Agrobacterium-mediated transformation. Under drought stress in the field, compared with wild-type, ectopic expression of Ac1-SST in cotton resulted in significantly higher soluble sugars (especially 1-kestose), proline and relative water contents, as well as decreased malondialdehyde content, which contributed to maintaining intracellular osmoregulation and reducing membrane damage. In addition, ectopic expression of Ac1-SST in cotton significantly improved the photosynthesis rate, performance of PSII (including Pn, Fv/Fm, WUE, ΦPSII, and PItotal) and plant growth under drought stress. Furthermore, compared with the wild-type, under the droughted field, the yield loss per square meter of transgenic cotton was reduced by an average of 20.9% over two consecutive years. Our results indicate that the Ac1-SST gene can be used to improve drought tolerance and yield of cotton varieties, and might also be a promising drought-resistant gene for improving other crop varieties.